The 80s loop of the catalytic chain of Escherichia coli aspartate transcarbamoylase is critical for catalysis and homotropic cooperativity. - Macol, C. (Cold Spring Harbor Laboratory Press, 1999)
The X-ray structure of the Escherichia coli aspartate transcarbamoylase with the bisubstrate analog phosphonacetyl-L-aspartate (PALA) bound shows that PALA interacts with Lys84 from an adjacent catalytic chain. To probe the function of Lys84, site-specific mutagenesis was used to convert Lys84 to alanine, threonine, and asparagine. The K84N and K84T enzymes exhibited 0.08 and 0.29% of the activity of the wild-type enzyme, respectively. However, the K84A enzyme retained 12% of the activity of the wild-type enzyme. For each of these enzymes, the affinity for aspartate was reduced 5- to 10-fold, and the affinity for carbamoyl phosphate was reduced 10- to 30-fold. The enzymes K84N and K84T exhibited no appreciable cooperativity, whereas the K84A enzyme exhibited a Hill coefficient of 1.8. The residual cooperativity and enhanced activity of the K84A enzyme suggest that in this enzyme another mechanism functions to restore catalytic activity. Modeling studies as well as molecular dynamics simulations suggest that in the case of only the K84A enzyme, the lysine residue at position 83 can reorient into the active site and complement for the loss of Lys84. This hypothesis was tested by the creation and analysis of the K83A enzyme and a double mutant enzyme (DM) that has both Lys83 and Lys84 replaced by alanine. The DM enzyme has no cooperativity and exhibited 0.18% of wild-type activity, while the K83A enzyme exhibited 61% of wild-type activity. These data suggest that Lys84 is not only catalytically important, but is also essential for binding both substrates and creation of the high-activity, high-affinity active site. Since low-angle X-ray scattering demonstrated that the mutant enzymes can be converted to the R-structural state, the loss of cooperativity must be related to the inability of these mutant enzymes to form the high-activity, high-affinity active site characteristic of the R-functional state of the enzyme.